Characterization of Forskolin-Induced Ca2+ Signals in Rat Olfactory Receptor Neurons - Ken-ichi Otsuguro; Shree Hari Gautam; Shigeo Ito; Yoshiaki Habara; Toshiyuki Saito (Elsevier, 2005)
Forskolin-induced Ca2+ signals were examined in isolated rat olfactory receptor neurons (ORNs) using a Ca2+ indicator, fura-2. In the soma of the ORNs, forskolin caused an increase in the intracellular Ca2+ concentration ([Ca2+]i) that was enhanced by a phosphodiesterase (PDE) 1 inhibitor, 8-methoxymethyl-3-isobutyl-1-methyl-xanthine, but not a PDE4 inhibitor, rolipram. Forskolin-induced Ca2+ signals were abolished with the removal of extracellular Ca2+ and un-affected by treatment with thapsigargin or caffeine plus ryanodine. Niflumic acid, a Ca2+-activated Cl- channel inhibitor, or nifedipine, an L-type Ca2+ channel inhibitor, slowed the initial rate of the increase in [Ca2+]i in response to forskolin. Nifedipine did not affect the increase in [Ca2+]i that was slowed by niflumic acid. In Ca2+ measurements with a confocal microscope and a calcium indicator, Fluo-4, the onset of the response to forskolin in the knob region occurred simultaneously or earlier, but not later, than that in the soma. It is suggested that the forskolin-induced Ca2+ signals are due to Ca2+ influx, but not the release of Ca2+ from Ca2+ stores, and that the initial rapid increase in [Ca2+]i is associated with the activation of the voltage-dependent Ca2+ channels in rat ORNs. Keywords:: olfactory receptor neuron, forskolin, Ca2+ signal, phosphodiesterase, Ca2+ channel